Comparison of Open Craniotomy vs Conservative Treatment in Minor Spontaneous Intracerebral Hemorrhage (ICH) : A Comprehensive Systematic Review - Pratiwi, Riska; Ibrahim, Sabri; Kausar, Teuku Akmal (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes in the USA, Europe, and Australia, and 20–30% of Asian cases, with a30-day mortality rate of 35% to 52%; half of the related deaths occur in the first 2 days. Its overall incidence is 24.6 per 100,000 person-years, indicating that it represents the most fatal type of stroke around the world. Methods: The aim of study of this study is to investigate the comparison of open craniotomy vs conservative treatment in minor spontaneous intracerebral hemorrhage (ICH). This study used the systematic review method by discovering articles using the search engines PubMed, SagePub, and Science Direct, and 5 articles met the inclusion criteria in this study. Results: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Surgical management of intracerebral hemorrhage has unique advantages as it can remove the hematoma effectively and decrease intracranial pressure and the incidence of complications. Keywords: Intracerebral hemorrhage (ICH); surgical; treatment; craniotomy; conservative.